Integrating Universal Design, Culturally Sustaining Practices, and Constructivism to Advance Inclusive Pedagogy in the Undergraduate Classroom - Tabitha Grier-Reed; Anne Williams-Wengerd (MDPI AG, 2018)
While primary and secondary teachers are legally required to adhere to inclusion guidelines for students experiencing disabilities, instructors in higher education have had more leeway to operate under a more traditional paradigm which can marginalize rather than include students in the classroom. Furthermore, students experience exclusion for reasons other than and in addition to disabilities, including, race, ethnicity, language, gender, and sexual orientation. Inorderto advance inclusion for all students in the higher education classroom, we propose integrating universal design, culturally sustaining pedagogy, and constructivist approaches to teaching and learning. We aim to not only forward an integrative theoretical framework for inclusive pedagogy grounded in a constructivist perspective, but to also provide practical strategies that promote a more inclusive undergraduate classroom.